In-vitro exposure to endocrine disruptors alters inflammatory markers in whole hypothalami and immortalized GnRH neurons - Riaño Gómez, Juan Manuel (2021)
Bisphenol A (BPA), a monomer of polycarbonate plastics, and Benzophenones (BPs), UV-filters, are endocrine disrupting chemicals (EDC). The hypothesis is that EDC exposure causes brain inflammation and predisposes animals to develop obesity and infertility. Previous results showed that the in-vitro exposure to BPA increases Glial Fibrillary Acidic Protein (GFAP) in hypothalami and IL-18 in mature GnRH neurons. Here, gene expression of cytokines (interleukins 6 and 1β, IL-6 and IL-1β) were evaluated in whole hypothalami of adult Balb/c mice and in immortalized GnRH neurons.